Impact of Spondyloarthritis on Pregnancy Outcome: A Descriptive Analysis from a Specialized Center in Qatar - Al Emadi S; Hadwan NN; Saleh R; Satti E; Singh R (Open Access Rheumatology: Research and Reviews, 2024)
Samar Al Emadi,1 Nawal Nouman Hadwan,1 Rawan Saleh,1 Eman Satti,1 Rajvir Singh2 1Department of Rheumatology, Hamad Medical Corporation, Doha, Qatar; 2Medical Research Center, Statistics, Hamad Medical Corporation, Doha, QatarCorrespondence: Samar Al Emadi, Department of Rheumatology, Hamad General Hospital, PO Box 3050, Doha, Qatar, Tel +974 55550087, Email salemadi@hamad.qaIntroduction: Spondyloarthritis (SpA) most commonly presents at childbearing age; thus, pregnancy is of concern. However, data on pregnancy outcomes in these patients are limited.Purpose: This study aimed to retrospectively describe pregnancy outcomes in patients with SpA from the Middle East.Patients and Methods: We reviewed the electronic health records of all pregnant women attending a specialized pregnancy and rheumatic disease clinic between 2016 and 2022. All pregnant patients diagnosed with axial spondyloarthritis (axSpA) and peripheral SpA were included. Data on adverse maternal and fetal outcomes were collected.Results: Fifty-seven eligible pregnancies were identified from hospital records: 10 pregnancies ended in early miscarriage. Forty-seven pregnancies resulted in live singleton births, 25 in patients with peripheral SpA and 22 with axSpA. Human leukocyte antigen B27 was positive in 7 (15%) patients and only in women with axSpA. Twenty-nine (64%) patients received treatment throughout pregnancy. Consistent biologic disease-modifying antirheumatic drug (bDMARD) use was high, in eight (32%) patients with peripheral SpA and in nine (41%) with axSpA. A conventional synthetic disease-modifying anti-rheumatic drug (csDMARD) was used as treatment in 11 (50%) patients with peripheral SpA and two (8%) with axSpA. Twenty-two (53%) neonates were delivered by cesarean section, 19 (40%) by normal vaginal delivery and three (6%) by assisted delivery. Additionally, 44 (94%) deliveries were at term, and 42 (91%) neonates had a normal birth weight. Exploration of a subgroup showed no difference in reported outcomes between patients treated with bDMARD and those treated with csDMARD.Conclusion: This descriptive study reports a high rate of favorable pregnancy outcomes in patients with SpA. There was no evidence to suggest a difference in pregnancy outcomes between women with axSpA and those with peripheral SpA. This study was one of the first reports from the Middle East. Further studies with larger sample size are warranted.Keywords: axial spondyloarthritis, pregnancy, pregnancy outcomes, neonatal health, maternal health